Criando niños saludables: Comience con el desayuno: FCS8901-Span/FY1256, 10/2011 - Clinton, Rebecca A.; Shelnutt, Karla P. (EDIS, 2011)
¿Dentro de su rutina hay un desayuno saludable para toda la familia? This 4-page fact sheet is the Spanish-language version of Raising Healthy Children: Begin with Breakfast (FCS8901/FY11530). Written by Rebecca A. Clinton and Karla P. Shelnutt, and published by the UF Department of Family, Youth and Community Sciences, October 2011.